Synthesis of CuNP-modified carbon electrodes obtained by pyrolysis of paper - Duran, Gema M. (2016)
A one-step approach for the synthesis and integration of copper nanoparticles (CuNPs) onto paper-based carbon electrodes is herein reported. The method is based on the pyrolysis (1000 °C under a mixture of 95% Ar/5% H2 for 1 h) of paper strips modified with a saturated solution of CuSO4 and yields to the formation of abundant CuNPs on the surface of carbonized cellulose fibers. The resulting substrates were characterized by a combination of scanning electron microscopy, EDX, Raman spectroscopy as well as electrical and electrochemical techniques. Their potential application, as working electrodes for non-enzymatic amperometric determination of glucose, was then demonstrated (linear response up to 3 mM and a sensitivity of 460 ± 8 μA cm-2 mM-1). Besides being a simple and inexpensive process for the development of electrochemically-active substrates, this approach opens new possibilities for the in-situ synthesis of metallic nanoparticles without the traditional requirements of solutions and adjuvants.